Beragama Dalam Bingkai Media Sosial: Analisis Semiotika John Fiske Pada Akun Instagram @Hijrahsantun - Julita Lestari; Danil Folandra (Al-Adyan: Journal of Religious Studies, 2022)
This article aims to analyze the semiotics of Islamic posts on the Instagram account @hijrahsantun. This study is in the form of documentary research on posting pictures and narratives as well as netizen comments. The data in this study were collected through random screenshots and led to hijrah motivations and Islamic messages. In addition, the data in the form of journal books and relevant studies also enriched. The data was then analyzed using qualitative content analysis with a narrative method related to the text of the posts. This study finds first, at the level of reality there is the ability of polite hijrah account owners to align the message of da'wah with background taking. The two posts from the polite hijrah account represent religious issues that are considered trivial so that for readers they are used as religious reminder messages, John Fiske calls the representation stage. Third, there is the transmission of religious ideology that invites readers to emigrate. Therefore, for account owners, social media is a place for da'wah and ideological transmission, while for users, posts on the @hijrah polite account are used as a reminder of the value of normative worship. Tulisan ini bertujuan untuk manganalisis semiotik postingan islami pada akun instagram @hijrahsantun. Studi ini dalam bentuk penelitian dokumentasi terhadap postingan gambar dan narasi serta komentar netizen. Data dalam studi ini dikumpulkan melalui screenshoot secara acak dan mengarah pada motivasi hijrah serta pesan-pesan islami. Selain itu data berupa buku jurnal dan studi rerlevan turut memperkaya. Data tersebut kemudian dianalisis menggunakan content analysis kualitatif dengan metode naratif terkait teks dari postingan. Studi ini menemukan pertama, pada level realitas adanya kemampuan pemilik akun hijrah santun dalam penyelarasan antara pesan dakwah dengan pengambilan background. Kedua postingan dari akun hijrah santun merepresentasikan persoalan keagamaan yang dianggap sepele sehingga bagi pembaca dijadikan sebagai pesan-pesan pengingat keagamaan, John Fiske menyebut tahap representasi. Ketiga, adanya transmisi ideologi keagamaan yang mengajak pembaca untuk hijrah. Maka dari itu bagi pemilik akun, media sosial menjadi wadah dakwah serta transmisi ideologi sementara bagi pengguna, postingan pada akun @hijrah santun dijadikan sebagai pengingat nilai ibadah normatif.